Exploring the Impact of Artificial Intelligence on University Students' Perception of Slow Employment: A Psychological and Behavioral Analysis - Peng Yang; Xiaodie Wang; Jing Zhang; Sharmin Kutty Sivaraman; Pu Song, (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study explores the psychological effects of artificial intelligence (AI) tools on university students’ perceptions and experiences of slow employment. The aim is to understand how the use of AI tools influences students’ anxiety, stress, motivation, and decision-making confidence, as well as their coping strategies in the context of job search challenges. Using a mixed-methods approach, data were collected through quantitative surveys (n = 200) and qualitative interviews (n = 10), followed by behavioral and emotional analysis using AI-based sentiment and emotion recognition systems. Moreover, for quantitative data, regression analysis was performed to identify the factors that impacted the students’ psychological well-being. In contrast, for qualitative data, thematic analysis was employed to identify the psychological and emotional outcomes associated with slow employment. The findings show that AI tool usage significantly reduced anxiety, increased confidence, and enhanced students’ self-efficacy and motivation, while stress remained positively correlated with anxiety levels. The emotional analysis revealed dynamic shifts in emotional states, with anxiety decreasing and confidence increasing after the AI interaction. The study concludes that AI tools offer significant psychological support but require refinement in terms of personalization and transparency. The integration of AI tools with human support systems is essential for practical career guidance. This study offers novel insights into the impact of AI on emotional well-being and provides implications for enhancing career support systems for students.